Studies on the curing, tensile and adhesion characteristics of cushion gum to carcass in truck retreaded tires: the effect natural rubber types. Issue 1 (January 2022) - Rahmaniar; Susanto, T; Marlina, P; Prasetya, H A; Purbaya, M
Abstract: In order to improve the quality of truck retreaded tyres, the cushion gum (CG) plays an important role as an adhesion medium to bond the carcass of the new tread to the worn old tyre. This study investigates the effect of natural rubber types such as reclaimed skimmed latex (RSL), ribbed smoke sheet (RSS), chloroprene (CR) and RSS added 10 phr of carbon black (CB) towards its CG performance in cold cure systems. The CG was compounded based on ASTM D3182 with 10 phr of Cumaroun Resin, 5 phr of Calcium Silicate, and other chemicals. The 4 types of CG were tested its physical and tensile properties. To determine the curing time, the rheological was analysed. The results show that the addition of carbon black may improve physical and tensile properties, excluding the elongation at break. It is found that the curing time of cushion gum based on SL rubber has the shortest duration. Each CG was applied to retreat the same type of truck's worn tyres (1000R20). After surface modification, 5 mm of CG was bonded new same carcass the old surface and continued by heating in the autoclave chamber for 3 hours with pressure at 2 atm. The results show that the adhesion strength of cushion gum based on RSL; RSS; CR; RSS/CB is as follows: 13.64; 8.21; 8.04; 8.01 kN/m respectively, while the adhesion strength of commercial cushion gum is 15, 38 kN/m. The spectra FTIR of each cushion gum convince that the less dispersion matrix compared to commercial cushion gum. To sum up, the RSL-NR is the recommended polymer for cushion gum compounding. However, in order to improve its quality, it is suggested to do some pre-treatment and increase the number of tackifier and processing oil in the formulation